Maksimalkan Pembelajaran Akidah Akhlak Dengan Media Audio Visual: Studi Pengaruh Terhadap Hasil Belajar - Ali Maulana, Muhammad Rizky; Huda, Miftahul; Kurniasih, Imas; Mukhlishah; Salam, Moch Fadlani (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Audio-visual learning media is a medium for distributing messages by utilizing the senses of hearing and vision. In the subject of moral creed, it becomes one of the bridges to improve student learning outcomes. Learning outcomes are the results achieved in the form of numbers or scores obtained after being given a learning outcome test at the end of each lesson. The use of audio-visual learning media in moral creed subjects can be a bridge to improve student learning outcomes.  Based on pre-observation during the Introduction to the Educational Environment (PLP) carried out at MAN 2 Bandung Bandung Regency, the author saw that learning in the subject of Akidah Akhlak had conducted learning using learning media. The sign is that MAN 2 Bandung Bandung Regency has implemented learning well. The purpose of this study was to determine 1) what percentage of the level of use of audio-visual learning media, 2) what percentage of student learning outcomes in the subject of akidah, 3) how much influence the use of audio-visual learning media has on student learning outcomes. This research uses quantitative methods with 36 respondents, and data collection tools in the form of observation, questionnaires and documentation. The results showed that: 1) The use of audio-visual learning media in the subject of akidah akhlak obtained a percentage value of 38% in the sufficient category; 2) Student learning outcomes in the subject of moral creed obtained a percentage value of 44.4% in the sufficient category; 3) The effect of the use of audio-visual learning media on student learning outcomes in moral creed subjects has a very significant effect with a percentage value of 94%.